The executive tricks of cultural advertising with an emphasis on interactive art in the years 2000-2020. (25th January 2022) - Shahraki, Mohsen Ali Babaei; Dastmardi, Abdul Khaliq; Rasoulipour, Somayeh
The concept of advertising means orienting oneself to public opinion; so today, mass media advertising, including urban advertising, which is one of the main sources of information, can promote the culture of a society. These media play an important role in changing the level of society's culture. In fact, media advertising has led to many changes in the lifestyle, values and culture of the audience. Therefore, in this research, an attempt has been made to examine the executive tricks in cultural advertising and its features in order to convey the message effectively to the audience. To achieve this goal, a descriptive-analytical method has been used and its information has been collected in a library manner. Finally, using the obtained data, the samples of the world's cultural and cultural urban advertisements were analysed. As the results of this study show, the method of interaction with executive techniques such as 'participatory art and volumetric art' has had the greatest impact on persuading the audience. This has been achieved through the participation and physical intervention of the audience with cultural advertising. Accordingly, such advertisements give better cultural themes to audience.